Diagnosis and treatment of gas-bloat syndrome after antireflux surgery - O. S. Tyvonchuk; I. S. Tereshkevych; R. I. Vynohradov; D. Yu. Zhytnik (Zaporožskij Medicinskij Žurnal)
The aim of the study was to assess the frequency of complications after laparoscopic Nissen fundoplication in patients with a hernia of the esophageal orifice of the diaphragm, to determine the features of diagnosis and treatment of gas-bloat syndrome.